Making Jey-Si (Jelly Siwalan) as A Siwalan Fruit Processing Innovation (In The Wife Group of Siwalan Traders in Panyuran Tuban) - Hendra Suwardana; Anggia Kalista; Krishna Tri Sanjaya (Kontribusia : Research Dissemination for Community Development, 2021)
Tuban Regency, especially Panyuran area, is the largest producer of Palm (Siwalan) fruit in Tuban. However, Siwalan fruit is less popular because it rots easily and how to consume it is difficult. For this reason, innovation is developed and introduces it to the public how to consume Siwalan fruit which is practical and in demand, one of which is by processing it into jelly candy. With this innovation, food security can last approximately 1 month without preservatives. This siwalan jelly candy is made with natural ingredients and attractive colors, so that it can increase the interest in public consumption, especially children, which has an impact on creating business opportunities to improve the community's economy.